PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR PKN PADA SISWA KELAS V MIN 34 ACEH BESAR - Khazinatul Asrar Khazinatul Asrar (lembaga Sepercenter, 2024)
Student learning success is greatly influenced by the learning model used by teachers. This study aims to improve teacher activity, student activity, and civic education learning outcomes through the application of the Numbered Head Together (NHT) cooperative learning model to fifth-grade students at MIN 34 Aceh Besar with the material ‘The Importance of Maintaining the Integrity of Indonesia.’ The NHT model is a cooperative learning strategy that uses numbering for students to encourage them to actively search for, process, and convey information in front of the class. This study used a Classroom Action Research (CAR) approach, which was carried out in two cycles. The research subjects were fifth-grade students at MIN 34 Aceh Besar. Data collection techniques were carried out through observation and tests, with instruments in the form of observation sheets of teacher and student activities and learning outcome test questions. Data analysis included teacher activities, student activities, and student learning outcomes. The results showed that teacher activity increased from a score of 3.17 (good category) in cycle I to 3.58 (very good category) in cycle II. Student activities also increased from a score of 2.94 (good category) to 3.76 (very good category). Student learning outcomes increased from an average of 53.12% (fair category) in cycle I to 70.31% (good category) in cycle II. Thus, the application of the NHT cooperative learning model has been proven to increase teacher and student activity as well as the learning outcomes of Grade V students at MIN 34 Aceh Besar.